British diplomacy towards Spanish involvement in the war of Polish succession (1733–1735) - Makówka, Magdalena (Władza i polityka w czasach nowożytnych. Dyplomacja i sprawy wewnętrzne, 2020)
The aim of this article is to present the attitude of Great Britain to Spanish involvement in the war of Polish succession. Benjamin Keene, an envoy to Spain, played a key role in the British policy of that period. The British decided not to get involved in the conflict and from its first months tried to persuade Spain not to participate in it. Since 1734, the British together with the Dutch tried to mediate for peace. However, these efforts proved to be ineffective and did not bring any benefits to Albion.